Hukum Mendidik Istri Dan Anak Perspektif Hadis Nabi Dalam Kutub Al-Tis'ah - nurhadi, nurhadi (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2020)
This article aims to examine further the concept of education according to Islamic teachings, both within and outside the family. This study was carried out because it remembers that, in the provisions of Islamic Law, especially Islamic law which is sourced from the hadith of the Prophet Muhammad SAW which is at the pole of al-Tis'ah, education in the family is the duty and responsibility of the head of the family. From the analysis of 69 hadiths, there are two main traditions discussed regarding the law of educating wives and children for heads of families. According to the hadith of the Prophet Muhammad in the Pole Al-Tis'ah, (narrated by Tirmizi No. 2577 and Muslim No. 2137, it can be concluded that educating wives and children is fardhu ain or compulsory for the head of the family as a form of responsibility for providing spiritual sustenance (knowledge religion) to family members (the wife and childrens).